Proanthocyanidin in red rice inhibits MDA-MB-231 breast cancer cell invasion via the expression control of invasive proteins - Komsak Pintha (2018)
© 2015 The Pharmaceutical Society of Japan. Proanthocyanidin is one of the main active compounds found in red jasmine rice. We previously reported that red rice extract could reduce cancer cell invasion. However, the direct effect of proanthocyanidin from red rice on the invasion of cancer cells and the exact molecular mechanism remained unclear. Here, we report for the first time that proanthocyanidin-rich fraction from red rice (PRFR) reduced the migration and invasion of MDA-MB-231 human breast cancer cells. The types of proanthocyanidin in PRFR were identified as procyanidins and prodelphinidins by acid hydrolysis. For cancer cell invasion, degradation of the extracellular matrix (ECM) is required. Treatment of the cells with PRFR reduced the expression of ECM degradation-associated proteins, including matrix metalloproteinase-9 (MMP-9), membrane type-1 matrix metalloproteinase, urokinase plasminogen activator, urokinase plasminogen activator receptor and plasminogen activator-1. Moreover, PRFR also reduced the activity of collagenase and MMP-9. Furthermore, PRFR significantly suppressed the expression of intercellular adhesion molecule-1 and interleukin-6. We also found that PRFR reduced the DNA-binding activity of nuclear factor kappa B (NF-κB), which is the expressed mediator of ECM degradation-associated proteins. These results suggest that proanthocyanidin from red rice mediates MDA-MB-231 breast cancer cell invasion by altering the expression of the invasion-associated proteins, possibly by targeting NF-κB activity.